Estimativa da pegada hídrica no campus da UNICAMP - Justo, André de Souza; Teruel, Bárbara J.; Guillardi Junior, Hildo (International Workshop for Innovation in Safe Drinking Water, 2022)
The water footprint is qualitative and quantitative indicator of water use, which can be defined as the total volume of water used, direct and indirect (water consumption that is measured, and that implicit in the production of goods and services). The index provides managers with a measurable indicator for decision-making in the management of water resources. The research sought to calculate the water footprint of the Barão Geraldo campus, University of Campinas (Unicamp) development a platform, fed with data on water consumption, quantity of meals, and other items, provided by the responsible sector in Unicamp. From the access to the water footprint indices and estimates, technological actions and aimed at sustainability actions can be implemented, incorporating the pillars environmental, social and governance factors into water management.